1983
DOI: 10.1002/neu.480140605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fatty acids on the membrane fluidity of cultured chick dorsal root ganglion measured by fluorescence photobleaching recovery

Abstract: The effect of fatty acids on the membrane fluidity in tissue cultured chick embryo dorsal root ganglion was studied by fluorescence recovery method. Lateral motion of the lipid was measured by observing the fluorescent probe, 5-(octadecylthiocarbamoylamino) fluorescence, F18. The effective lateral diffusion coefficient of the membrane was around 0.30 X 10(-8) cm2/sec in control cells, 0.42 X 10(-8) cm2/sec in 2-decenoic acid treated cells, and 0.35 X 10(-8) cm2/sec in valeric acid treated cells. From these res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Takenaka et al (1987) saw no difference between saturated and unsaturated fatty acids in the attenuation of Na+ current, and attributed their effect to a disruption of the Na+ channel m gate produced by fluidization of the membrane. This attribution is supported by measurements which show increases in membrane fluidity as measured by fluorescence photobleaching recovery (Takenaka et al 1983), as well as cell membrane expansion (Horie, Kawasaki & Takenaka, 1987), following application of millimolar quantities of 2-decenoate (CII: 1), a compound shown to reduce Na+ current. When comparing the present results with those of Takenaka et al (1987) it is clear that they differ significantly in terms of effect (attenuation of Na+ current with a shift in activation kinetics) and in the means of their production (millimolar quantities of lipid).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Takenaka et al (1987) saw no difference between saturated and unsaturated fatty acids in the attenuation of Na+ current, and attributed their effect to a disruption of the Na+ channel m gate produced by fluidization of the membrane. This attribution is supported by measurements which show increases in membrane fluidity as measured by fluorescence photobleaching recovery (Takenaka et al 1983), as well as cell membrane expansion (Horie, Kawasaki & Takenaka, 1987), following application of millimolar quantities of 2-decenoate (CII: 1), a compound shown to reduce Na+ current. When comparing the present results with those of Takenaka et al (1987) it is clear that they differ significantly in terms of effect (attenuation of Na+ current with a shift in activation kinetics) and in the means of their production (millimolar quantities of lipid).…”
mentioning
confidence: 86%
“…First, cis-fatty acids have been demonstrated to activate PKC in the absence of Ca2+ and phospholipid (Murakami & Routtenberg, 1985;Murakami et al 1986). Secondly, cis-fatty acids in monomeric form have been demonstrated to fluidize cellular membranes (Ahkong, Fisher, Tampion & Lucy, 1973;Takenaka, Horie & Kawasaki, 1983;Kitagawa, Endo & Kametani, 1985). Thirdly, cis-fatty acids, like all fatty acids, have the capacity to form micelles, which by fusing with the cellular membrane may disrupt membrane and ion channel function.…”
Section: Solutionsmentioning
confidence: 99%
“…Some change in the steadystate properties of the membrane must be considered and obvious candidates are the surface free energy or surface tension, and the dipole potential at the surface. We have found that fatty acids increase membrane fluidity (Takenaka, Horie & Kawasaki, 1983). The lipid lateral motion of the membrane complex was increased about 40% by the application of 2-decenoic acid, whereas valeric acid caused much smaller changes in the lateral motion of the membrane lipids.…”
Section: Hodgkin-huxley Parameters and Membrane Fluiditymentioning
confidence: 98%
“…The physiological meaning of this shift is not yet clear but some change in the steady-state properties of the membrane must be considered and obvious candidates are the surface-free energy or surface tension and the dipole potential at the surface. The lipid lateral motion of the membrane complex was increased enormously by the application of mediumchain fatty acids (Takenaka, Horie & Kawasaki, 1983;Takenaka, et al, 1986). The suppression mechanism of the long-chain fatty acids might be the same as that of the medium-chain fatty acids (Takenaka et al, 1987).…”
Section: Hodgkin-huxley Parameter Of Long-chain Fatty Acidsmentioning
confidence: 99%